The Effects of Extraction and Nonextraction Treatment on RME Applied Patients - Nihal Hamamcı; Atılım Akkurt; Mehmet Doğru; İlknur Veli; Orhan Hamamcı (Galenos Yayinevi, 2010)
Aim:The aim of this study was to compare the dentoalveolar, skeletal and soft tissue effects of upper two premolar extraction or nonextraction treatments after Rapid Maxillary Expansion (RME).Subjects and Methods:The sample of this study consisted of pre and posttreatment lateral cephalometric radiographs of 21 patients characterized by narrow maxilla and treated with or without extraction following RME. In our study, RME applied patients were divided into two groups as extraction and nonextraction. After adequate expansion and retention period, two upper first premolars were extracted in extraction group and no teeth were extracted in nonextraction group. Thereafter, fixed orthodontic treatment was started in two groups.Results:At the end of treatment when extraction and nonex-traction groups were compared, significant differences in A1 inclination to A-Po angle (p < 0.01), A1 to A-Po plane (p < 0.05) and B1 to A-Po plane distance (p < 0.05) representing the dentoalveolar incisor position were detected. Also statistically no significant differences were found between parameters related to lips or soft tissues. Our results do not support the idea that more retrusive profile occurs as a result of upper extraction treatment.Conclusions:In the light of these results, it is possible to say that there is no esthetic difference between the RME appliances applied patients treated by either upper premolar extraction or nonextraction treatment.